Tuberculosis of man and animals in Daghestan republic - R. A. Nuratinov; F. I. Islamova (Юг России: экология, развитие)
Retrospective analysis of epidemic-epizootic process of tuberculosis ant the data of the authors’ researches show the wideness of the morbidity among population and animals in Daghestan republic. Some points of connection of a man’s and animals’ tuberculosis are revealed.